2006
DOI: 10.47102/annals-acadmedsg.v35n4p279
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hypersensitivity Reaction After Intravenous Glucagon Administered for a Barium Enema: A Case Report

Abstract: Introduction: Few reports have documented allergic hypersensitivity reactions after barium gastrointestinal studies. Of these, the barium suspension, its additives or intravenous glucagon given for bowel relaxation has been implicated as possible allergens. We report a patient with delayed hypersensitivity reaction after barium enema and discuss the reasons supporting glucagon as the possible allergen. Clinical Picture: A 74-year-old Chinese woman presented with pruritic rashes, 1 day after a barium enema. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…[57][58][59] Additionally, glucagon may cause nausea, vomiting, delayed hypoglycemia, and allergic reactions. [60,61] A previous clinical trial showed that gastric peristalsis inhibitors did not improve the detection rate of early gastric cancer. [62] Clinical question 3.3: Can painless endoscopy improve the detection rate of early gastric cancer?…”
Section: Clinical Question 23mentioning
confidence: 99%
“…[57][58][59] Additionally, glucagon may cause nausea, vomiting, delayed hypoglycemia, and allergic reactions. [60,61] A previous clinical trial showed that gastric peristalsis inhibitors did not improve the detection rate of early gastric cancer. [62] Clinical question 3.3: Can painless endoscopy improve the detection rate of early gastric cancer?…”
Section: Clinical Question 23mentioning
confidence: 99%